1980
DOI: 10.1051/rnd:19800404
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diet and ovariectomy on adipose tissue cellularity in mice

Abstract: Summary. Three-week old female mice were ovariectomized. From weaning at 4 weeks they were fed either a control or a high fat diet. When 32 weeks old, the ovariectomized mice weighed more than the sham-operated ones, whichever diet they were fed. Food intake decreased 140 da x s after castration . Ovariectomized mice fed the control diet showed fat cell hypertrophy at three sites and hyperplasia of the perirenal tissue. In mice fed the fat-rich diet, ovariectomy only caused further hypertrophy in the subcutane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 11 publications
1
17
0
Order By: Relevance
“…1,2 E 2 replacement therapy can normalize these abnormalities by reducing food intake and increasing metabolic expenditure. 1,2 This anorexigenic role of E 2 has also been shown in rodent studies. [3][4][5] Ovariectomized rats display increase in food intake and adipose tissue deposition, which can be readily reversed with the re-introduction of E 2 .…”
Section: Introductionmentioning
confidence: 79%
“…1,2 E 2 replacement therapy can normalize these abnormalities by reducing food intake and increasing metabolic expenditure. 1,2 This anorexigenic role of E 2 has also been shown in rodent studies. [3][4][5] Ovariectomized rats display increase in food intake and adipose tissue deposition, which can be readily reversed with the re-introduction of E 2 .…”
Section: Introductionmentioning
confidence: 79%
“…Moreover, our findings are in line with the metabolic functions of estrogen and NPY. While estrogen has been demonstrated to exert anorexigenic effects (85,100,195,198), NPY is a known orexigen (44,231,232). Indeed, several lines of evidence suggest that estrogen mediates its anorexigenic effects through hypothalamic NPY (25,218).…”
Section: New Insights Into Reproduction Using Neuronal Cell Modelsmentioning
confidence: 96%
“…This view is supported by the work of Beretta et al who found that central administration of an adeno-associated viral vector encoding LIF did not affect UCP1 protein expression (11), whereas it has been reported that LIF decreases food intake (24), suggesting that LIF induces weight loss mainly through reduced appetite. Ovariectomy, on the other hand, has been reported to increase food intake in mice (25).…”
Section: Discussionmentioning
confidence: 99%